Ecophysiological variation of transpiration of pine forests: synthesis of new and published results. Issue 1 (January 2017) - Tor‐ngern, Pantana; Oren, Ram; Oishi, Andrew C.; Uebelherr, Joshua M.; Palmroth, Sari; Tarvainen, Lasse; Ottosson‐Löfvenius, Mikaell; Linder, Sune; Domec, Jean‐Christophe; Näsholm, Torgny
Abstract: Canopy transpiration ( E C ) is a large fraction of evapotranspiration, integrating physical and biological processes within the energy, water, and carbon cycles of forests. Quantifying E C is of both scientific and practical importance, providing information relevant to questions ranging from energy partitioning to ecosystem services, such as primary productivity and water yield. We estimated E C of four pine stands differing in age and growing on sandy soils. The stands consisted of two wide‐ranging conifer species: Pinus taeda and Pinus sylvestris, in temperate and boreal zones, respectively. Combining results from these and published studies on all soil types, we derived an approach to estimate daily E C of pine forests, representing a wide range of conditions from 35° S to 64° N latitude. During the growing season and under moist soils, maximum daily E C ( E Cm ) at day‐length normalized vapor pressure deficit of 1 kPa ( E Cm‐ref ) increased by 0.55 ± 0.02 (mean ± SE) mm/d for each unit increase of leaf area index ( L ) up to L  = ~5, showing no sign of saturation within this range of quickly rising mutual shading. The initial rise of E Cm with atmospheric demand was linearly related to E Cm‐ref . Both relations were unaffected by soil type. Consistent with theoretical prediction, daily E C was sensitive to decreasing soil moisture at an earlier point of relative extractable water in loamy than sandy soils. Our finding facilitates the estimation of daily E C of wide‐ranging pine forests using remotely sensed L and meteorological data. We advocate an assembly of worldwide sap flux database for further evaluation of this approach.